Vietnam and the West - Gadkar-Wilcox, Wynn, 1974- (Book collections on Project MUSE., 2010)
Early studies of Vietnam's relationship with the West tended to focus on the country's political and military responses to the aggressions of foreign powers, such as those marking the French colonial period (1862-1954) and the U.S.-Vietnam war. The nine essays in this volume take a different approach. Rather than assuming a clash between Vietnamese and Western civilizations, they examine the ways in which the Vietnamese have reformulated conceptions of the West within their own cultural context. In essays examining Catholicism, medicine, literature, gender relations, labor unions, the "third force," Agent Orange, and contemporary water rights, the contributors show how the Vietnamese have adapted and integrated Western ideas from the sixteenth century onward. Drawing on in-depth fieldwork and archival research in Vietnam, France, and the United Atates, the essays in this volume explore interactions between Vietnam and the West that have spanned many generations and shaped Vietnamese responses to the wars of the twentieth century. This volume illuminates the complex historical background of the region's colonial and postcolonial conflicts by avoiding Eurocentric assumptions about the "Vietnamese response" or "Vietnamese modernization," while retaining a concern for the centrality of indigenous identities and culture. Vietnam and the West revises our understanding of the reasons for the tragic conflicts in twentieth-century Vietnam.